Nursing of a patient with acute mastitis during lactation treated by milk-ejection manipulation technique combined with external application of Rutong powder (手法排乳联合乳通散外敷治疗哺乳期急性乳腺炎1例的护理体会) - ZHENG Hongmei (郑红梅); HE Jing (何静); JIA Ruijing (贾瑞晶); HUANG Qianqian (黄芊芊); TANG Ling (唐玲); CHEN Hong (陈宏) (中西医结合护理)
This paper summarized the clinical observation and nursing measures of a patient with acute mastitis during lactation treated by milk-ejection manipulation technique combined with external application of Rutong powder. On the basis of nursing assessment and basic care, the milk-ejection manipulation technique combined with external application of Rutong powder showed a positive effect on relief of pain and anxiety of the patient during lactation. This method has the advantages of few side effects, high safety and high patient acceptance. (本文总结1例哺乳期急性乳腺炎患者行手法排乳联合自制乳通散外敷治疗的效果及护理措施。在完善护理评估和常规护理的基础上, 手法排乳联合乳通散外敷治疗能够有效缓解患者疼痛和焦虑症状, 且该方法具有不良反应少、安全性高等优势, 患者易于接受。)